2015
DOI: 10.2471/blt.14.150037
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, cash transfers and health

Abstract: The forecast consequences of climate change on human health are profound, especially in low- and middle-income countries and among the most disadvantaged populations. Innovative policy tools are needed to address the adverse health effects of climate change. Cash transfers are established policy tools for protecting population health before, during and after climate-related disasters. For example, the Ethiopian Productive Safety Net Programme provides cash transfers to reduce food insecurity resulting from dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Previous studies and systematic reviews have demonstrated the benefits of cash interventions on mitigating the health impacts from climate change, improving nutrition and advancing maternal health if markets are functional and quality services are available 7–9. Likewise cash transfers can improve outcomes by increasing consumption of nutritious foods as well as access to preventative care and vaccinations 10–12.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies and systematic reviews have demonstrated the benefits of cash interventions on mitigating the health impacts from climate change, improving nutrition and advancing maternal health if markets are functional and quality services are available 7–9. Likewise cash transfers can improve outcomes by increasing consumption of nutritious foods as well as access to preventative care and vaccinations 10–12.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, poverty alleviation programmes are promising avenues to increase population‐level resilience through reductions in vulnerabilities 52 . CTs effectively address key social determinants of health, 53 enabling families to be proactive against the direct and indirect effects of heat stress on health 54 . CTs have been shown to improve food security, nutrition, and dietary diversity, enhance women's empowerment, and increase use of healthcare services, including delivery in health facilities 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…An additional resource that has relevance to the clinical setting is from the World Health Organization and International Labor Organization (WHO/ILO), which has published pairs of selected workplace exposures and associated outcome pairings important for mortality related to occupational illnesses and injuries 203,204 . This includes the association of asbestos with cancers of the trachea, bronchus, lung, ovary, larynx, and mesothelioma 204 .…”
Section: Discussionmentioning
confidence: 99%